Monte Carlo studies of the three-dimensional Ising model in equilibrium - Hasenbusch, Martin (International journal of modern physics. C, Computational physics and physical computation, 2001)
We review Monte Carlo simulations of the Ising model and similar models in three dimensions that were performed in the last decade. Only recently, Monte Carlo simulations provide more accurate resu...